Agitations in the North and Niger-Delta of Nigeria up to 2007: Confrontation or Competition? - Abdulkadir Aikoye , Baba (Kashere Journal of Humanities, Management and Social Sciences, 2022)
The Niger Delta region has had serious, perhaps, dynamic grievances from the period before independence up to the present. As dynamic as these grievances are, so are their agitations and demands. It is argued that although the bulk of crude oil is derived from their lands, their area remains backward, underdeveloped and politically marginalized in the Nigerian Federation. They accuse the major ethnic groups of using oil wealth to develop their areas at the expense of the areas from which oil is derived. Another accusation is that several years of oil exploration and exploitation and the hazards of spillage and gas flaring which accompany it have degraded their environments. This has left their environment nearly uninhabitable. Their main occupations –farming and fishing –have been crippled; they have continued to lack basic infrastructure and amenities such as electricity, roads, schools, hospitals and potable water. Thus, grievances have been directed against both the Nigerian state and the oil companies, who have been accused of contributing too little in return for the huge profit they get from oil exploration. This paper, therefore, seeks to analyze the Niger Delta agitations based on these grievances and the reactions of the north. It reveals that the north has over time felt threatened in view of the economic and political implications of these agitations. Thus, they have reacted individually and collectively. The net effect of this is intensified search for “Northern Oil”, “competitive militancy” and tension in the body polity. It is the position of this paper that the reaction of the north to Niger Delta agitations, though seems to be a threat to the body polity at present, could produce the true Nigerian federation in the long run. Then, the desired elements of true federalism such as resource control, meaningful competitiveness, economic complementarities, entrepreneurship, would emerge in place of greed, domination, selfishness, tension and conflicts.